1983
DOI: 10.1136/oem.40.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol on the kinetics of mandelic acid excretion in volunteers exposed to styrene vapour.

Abstract: ABsTRAcr The effect of a dose of alcohol on the kinetics of mandelic acid excretion in four volunteers exposed to 220 mg/m3 styrene has been investigated under controlled exposure chamber conditions. Ethanol inhibited the excretion of mandelic acid, so that the peak excretion was delayed from the end of the exposure period until three hours afterwards. One hour after administration of ethanol blood mandelic acid concentrations were 56% of the levels found during the alcohol-free control exposure, and this was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Since there was no ethanol used in the production process, the presence of ethanol in the breathin g zone (air sa mples) ind icated the int ake of a subs tantia l amo unt of alco hol by some workers be fore wor k or during the breaks. Wilson et al (12) and Berode et al ( 13) rep orted the kinetics of mandelic acid excretion to be substantially altered in hum an volunteers exposed to both styrene and ethanol. Also in this study, a highly significant interaction wa s found between alcoho l intake before or during work and styrene ex pos ure, a finding indicating that alco hol intake sig nificantly delays mand eli c acid excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Since there was no ethanol used in the production process, the presence of ethanol in the breathin g zone (air sa mples) ind icated the int ake of a subs tantia l amo unt of alco hol by some workers be fore wor k or during the breaks. Wilson et al (12) and Berode et al ( 13) rep orted the kinetics of mandelic acid excretion to be substantially altered in hum an volunteers exposed to both styrene and ethanol. Also in this study, a highly significant interaction wa s found between alcoho l intake before or during work and styrene ex pos ure, a finding indicating that alco hol intake sig nificantly delays mand eli c acid excretion.…”
Section: Discussionmentioning
confidence: 99%
“…However, recentl y, another reputable group in an equally well planned and executed stud y came to rather opposite conclusio ns (2). It would be interesting if Dr Gobba and his co-workers would comment on this work, and also, if they can, compare the slopes or intercepts of the regression lines given in these two studies on the relationship between air and urinary styrene concentrations (which are very similar in seve ral published studies on the relat ionship between airborne styrene and the urinary excret ion of mandel ic acid and phenylglyoxylic ac id (3)(4)(5)(6)(7) .…”
mentioning
confidence: 94%
“…The consumption of alcoholic beverages shortly before or during a workshift (or in model laboratory experiments) modifies urinary levels of metabolites of styrene (6), xylenes (7), trichloroethylene (8) and other solvents significantly. As to CH-one, CH, or CH-01, the reduction of CH-one to CH-01 (the primary step in the metabolism of CH-one) is catalyzed by ADH (9), while the oxidation of C H to CH-01 (the primary step in the metabolism of CH) is mediated by the P450 system enzymes (10).…”
mentioning
confidence: 99%